Capillary electrophoresis–electrospray ionization-mass spectrometry interfaces: Fundamental concepts and technical developments - Bonvin, Grégoire; Schappler, Julie; Rudaz, Serge (Journal of Chromatography A, 2012)
▸ The ESI process is deeply explained in the context of CE. ▸ The electrochemical processes involved in CE–ESI-MS are presented. ▸ CE–ESI-MS interfaces are classified based on their operating flow rates. ▸ Electrospray and nanospray interfaces and their applications are overviewed. Capillary electrophoresis (CE) hyphenated to electrospray ionization (ESI) mass spectrometry (MS) is a powerful tool for analyzing a wide variety of analytes in different matrices. The major issue with CE–ESI-MS lies in finding a suitable and versatile interface to ensure the best CE and ESI operations. Thus, the development and improvement of CE–ESI-MS interfaces have been the subjects of much research. The first part of the present review focuses on the fundamental aspects of the three steps of the ESI process, i.e., spray formation, droplet evolution, and the production of gas-phase ions. In the second part of the review, the electrochemical reactions involved in the ESI and CE processes and their influences on the sensitivity and performance are discussed in detail. Then, the existing interfaces are divided into two major classes according to their operating flow rate (electrospray vs. nanospray regime). The particular characteristics of these two regimes are discussed by considering their practical impacts on ionization and the MS response. Finally, the current CE–ESI-MS interfaces are summarized, including their major advantages, drawbacks, and fields of application.